Engaging Corporate Partners to Build Your 4-H Program: Tips for Success - Marissa Staffen; Amanda Meek; Beth Hecht; Patricia Anderson ([TEST] Journal of Extension, 2021)
This article discusses best practices learned from a corporate partnership between Bayer, 4-H county programs in Missouri, New Jersey, and Pennsylvania; and National 4-H Council. This corporate partnership has blossomed into a multi-level engagement that is offering unique opportunities for both Bayer and 4-H programs at the local and state level. Authors share lessons learned that can be utilized for colleagues to leverage mutually beneficial corporate partnership to expand their work in the community.
Keywords: 4-H; corporate partnership; youth-adult partnerships; Science Matters; corporate volunteers